Analisis Stabilitas KM. Rejeki Baru Kharisma Rute Tarakan – Tanjung Selor - Alamsyah, Alamsyah; Zulkarnaen, Zen; Suardi, Suardi (TEKNIK)
Ship stability that is not according to the IMO standard will make the ship capsize when operating. The purpose of this research is to determine the cause of the overturn in terms of the stability criteria of the ship. The method used is software  of simulation. Stability analysis is carried out with the load case that occurs in the field when an accident occurs and the ideal loadcase according to PM 104 2017 standards about’s the transportation of operation. The results showed is cargo of goods placed on the roof top (loadcase 1) based on the criteria of Intact Stability; area of the stability arm curve at heeling 0° ~ 30° = 0.9417 m.deg, area 0° ~ 40° = 1,0200 m.deg, 30° ~ 40° = 0.0783 m.deg, GZ value at heeling 30° = 0.029 m, angle of occurrence of maximum GZ = 21.8°, and the initial GMt value = 0.135 m, the results stated that all did not meet the Intact Stability code A.749 criteria, while in it was obtained cargo of goods placed in the hull (loadcase 2) based on Intact Stability; area of the stability arm curve at heeling 0° ~ 30° = 4.5338 m.deg, area 0° ~ 40° = 7.1643 m.deg, area 30° ~ 40° = 2.6305 m.deg, GZ value at heeling 30° = 0.265 m, angle of occurrence of maximum GZ = 34.5°, and the initial GMt value = 0.621 m, the results stated that all met the Intact Stability code A.749 criteria